ABC5 International Consensus Conference on Advanced Breast Cancer, Lisbon, 16 November 2019 - Untch, Michael; Würstlein, Rachel; Lüftner, Diana; Haidinger, Renate; Fasching, Peter A.; Augustin, Doris; Briest, Susanne; Ettl, Johannes; Förster, Frank; Kurbacher, Christian M.; Lück, Hans-Joachim; Marschner, Norbert; Müller, Lothar; Müller, Volkmar; Radke, Isabel; Ruckhäberle, Eugen; Scheffen, Iris; Schumacher-Wulf, Eva; Schwoerer, Moritz; Steinfeld-Birg, Dieter; Ziegler-Löhr, Katja; Thomssen, Christoph; Harbeck, Nadia (Geburtshilfe und Frauenheilkunde, 2020)
The Advanced Breast Cancer Fifth International Consensus Conference (ABC5) which focuses on the diagnosis and treatment of advanced breast cancer was held in Lisbon on November 14 – 16, 2019. The aim of the conference is to standardize the treatment of advanced breast cancer worldwide using evidence-based data and to ensure that patients with advanced breast disease anywhere in the world are treated appropriately and have access to the latest therapies. This year, the emphasis was on new developments and study results from patients with advanced breast cancer as well as precision medicine. The collaboration with patient advocates from all over the globe is also an important goal of the ABC Conference, which is why the international ABC panel also included a number of patient advocates. We present a commentary on the voting results of the ABC5 panelists in Lisbon by a working group of German breast cancer specialists together with the implications for routine clinical care in Germany. The commentary is based on the recommendations of the Breast Commission of the German Gynecological Oncology Working Group (AGO). This commentary is useful, it includes country-specific features for the ABC consensus.
Keywords: ABC5 consensus; advanced breast cancer; precision medicine; 2019 study data